1979
DOI: 10.1080/00222895.1979.10735177
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Choice Reaction Time Methods in the Study of Motor Programming

Abstract: In an extensive series of experiments Sternberg, Monsell, Knoll, and Wright (1978) reported that simple RT increased as a linear function of the number of items to be pronounced or typed. The present experiments replicate a portion of these results, but show that the effect is less general than may have been supposed. Since the effect does not occur in every case in which a response programming interpretation would predict it, this interpretation must be rejected. This conclusion is consistent with the viewpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 12 publications
3
20
0
Order By: Relevance
“…· As for sequence length, ·RT began to asymptote beyond four responses with late transition sequences as well as sequences containing two or three different postures which was inconsistent with the Sternberg, Mansell, Knoll, and Wright (1978) studies. Nonmonotonic ef· fects of sequence' length on RT have been reported elsewhere (Hulstijn & van Galen, 1983;Klapp et al, 1979), and a recent typing study showed that the latency of the first keystroke was independent of word length (Salthouse, 1984). Thus, linear sequence length effects may be less general and may only under special circumstances extend beyond four responses.…”
Section: Resultsmentioning
confidence: 86%
“…· As for sequence length, ·RT began to asymptote beyond four responses with late transition sequences as well as sequences containing two or three different postures which was inconsistent with the Sternberg, Mansell, Knoll, and Wright (1978) studies. Nonmonotonic ef· fects of sequence' length on RT have been reported elsewhere (Hulstijn & van Galen, 1983;Klapp et al, 1979), and a recent typing study showed that the latency of the first keystroke was independent of word length (Salthouse, 1984). Thus, linear sequence length effects may be less general and may only under special circumstances extend beyond four responses.…”
Section: Resultsmentioning
confidence: 86%
“…RT increases with the number of motor chunks (Henry & Rogers, 1960;Klapp et al, 1979;Rhodes et al, 2004;Sternberg, Monsell, Knoll, & Wright, 1978;van Mier & Hulstjin, 1993), so we expected longer RT with more motor chunks. If words are typed as single chunks, there should be no string length effect in RT to words.…”
Section: Methodsmentioning
confidence: 86%
“…In both Experiments 1 and 2, we examined chunking in motor planning. RT increases with the number of motor programs, or motor chunks, that need to be retrieved and loaded into a motor buffer (e.g., Henry & Rogers, 1960;Klapp et al, 1979). Experiments 3 and 4 investigated the effect of altering haptic feedback on hierarchical control in motor planning and STM.…”
Section: The Present Studymentioning
confidence: 99%
“…The fact that word size can influence both simple and choice reaction times is interesting, since it is argued that simple reaction times do not reflect influences of speech planning as such (e.g., Klapp et a}., 1979;Sheridan, 1981). In fact, a simple reaction time task is often used to avoid influences that are related to speech planning (cf.…”
mentioning
confidence: 99%
“…In fact, a simple reaction time task is often used to avoid influences that are related to speech planning (cf. Hulstijn, 1987;Klapp et al, 1979;Ludlow, 1991;Sternberg et a(., 1978;Watson & Alfonso, 1983. How then to explain the effect of word size on both simple and choice reaction times?…”
mentioning
confidence: 99%